Abordagem textual no ensino de latim - Longo, Giovanna [UNESP] (My University, 2014)
The study of Latin is essentially focused on the receptive writing skills acquisition. For this reason, the teaching of this ancient language should have the readers’ training as its main objective. ! e e" ective understanding of ancient texts depends on a learning process that is based on three competence levels: the language level, the textual level and the intertextual level. As part of this teaching methodology, which seeks to narrow the cultural gap between the ancient and the contemporary world, avoiding anachronistic interpretation of Latin texts, this paper presents strategies that allow students to learn grammar from authentic texts.

O estudo do latim está essencialmente voltado à aquisição de uma competência receptiva escrita. Por essa razão, o ensino dessa língua antiga deve ter como objetivo principal a formação de leitores. A e caz compreensão de textos antigos depende de um processo de aprendizagem que passe por três níveis de competência: o nível linguístico, o nível textual e o nível intertextual. Como parte desse encaminhamento metodológico para o ensino de latim, que procura estreitar o distanciamento cultural existente entre o mundo antigo e o contemporâneo, evitando anacronismos na leitura e na interpretação de textos latinos, apresentam-se estratégias que permitem trabalhar com o estudo da gramática sem dissociá-la da leitura de textos autênticos.
Textual approach in latin teaching
Keywords: Latin language; Education; Reading; Classical Culture; Língua Latina; Ensino; Leitura; Cultura Clássica